PBL-STEM Modul Feasibility Test for Preservice Biology Teacher - Endang Setyaningsih; Putri Agustina; Sofyan Anif; Che Nidzam Che Ahmad; Iyan Sofyan; Alanindra Saputra; Wan Nasriha Wan Mohamed Salleh; Destama Einstein Shodiq; Sania Rahayu; Muhammad Luthfi Hidayat (Universitas Muhammadiyah Surakarta, 2022)
Life skills are needed in this era of globalization to be successful in the school environment or outside of school. According to the 2019 World Economic Forum, the world's demand for STEM qualifications and skills is very high now and is likely to continue to increase in the future. Today, 75% of the fastest-growing industrial-scale jobs require skilled STEM workers. Faced with this, to be able to compete, the world of work requires people who can adapt to their new work environment. STEM can empower individuals with the skills to succeed and adapt to new work environments. To get individuals who have STEM skills, individuals who have 21st-century skills are needed. This is because in 21st-century skills 3 skills must be met, namely learning skills, reading and writing skills, and life skills. The purpose of this study was to determine the feasibility of the PBL-STEM module developed for prospective Biology teacher students as an effort to improve 21st-century skills. The method used was the Rosset-based RnD ADDIE model. The ADDIE Teaching Model includes 5 stages, namely analysis, design, development, implementation, and evaluation. The results of the material expert validation show that the average score of the material expert validation results shows a fairly good category with an average of 2.94. The results of practitioner validation show that the average score of practitioner validation results shows a good category with an average of 3.56. The results of the small group readability test showed that the average score on the small group readability test was in the good category with an average score of 3.39.